Lack Of Information as part of the Lack Of Democracy in The European Union - Sotelo González, Joaquín (2022)
The basis of the present European Union was founded on the creation of the European Communities, which came into being in the middle of the 20th century. During this long period of time, this ambitious programme of international integration was led in an elitist and technocratic manner, and on many occasions, even turning its back to public opinion. From the middle of the 1980s, more in-depth studies have been carried out on the project, whose scope has gradually extended to the daily lives of its citizens. It is then when European authorities start to perceive the dangerous “division” between elitists and citizens.